When Capital Matters More Than Commitment: CSR Disclosure and Bank Performance in an Emerging Market - Nabella, Septa Diana; Raharjo, Dwi Sihono; Hakim, Luqman (International Review of Management and Marketing, 2026)
This study examines whether corporate social responsibility disclosure (CSRD) in emerging market banking reflects strategic sustainability commitment or is primarily driven by financial capacity. Using panel data from 13 large Indonesian conventional banks (KBMI III and IV) over the 2019–2023 period, we analyse the determinants of CSR disclosure and its relationship with bank financial performance. Fixed-effects regression results show that capital adequacy and bank size are significant positive drivers of CSR disclosure, while credit risk, liquidity, and macroeconomic conditions are not. Moreover, CSR disclosure does not have a statistically significant effect on bank profitability, measured by return on assets, and does not mediate the relationship between bank-specific characteristics and financial performance. These findings indicate that CSR disclosure in a highly regulated emerging market banking system is largely shaped by financial capacity and institutional scale rather than by value-creating sustainability strategies. The study contributes to the banking literature by highlighting the contextual limits of the CSR performance nexus and the role of regulation in standardising non-financial disclosure practices.